Spectacular nature : corporate culture and the Sea World experience - Davis, Susan G., 1953- (University of California Press, 1997)
"This is the story of Sea World, a theme park where nature itself is on display, where the wonders of marine life are marketed to an audience hungry to discover new worlds. Drawing on ethnographic research, history, and cultural criticism, Susan Davis reads Sea World as an industrial landscape and a postmodern phenomenon. Included in the price of admission, she finds, is a heavy dose of public relations, advertising, and environmentalism, corporate-style."--Jacket